Bakery products with dietary supplements for a healthy diet - L. A. Avetisyan; O. P. Khrapko (Новые технологии, 2024)
Nowadays a healthy diet plays a very important role in the nutrition of people of every age group. In the context of constant growth in demand for healthy food products, it is important to expand the range of products with functional properties. Naturally enriched foods can not only maintain health, but also improve it. Pectin extract is a natural complexing agent, capable of removing toxic substances, heavy metals and radionuclides from the body. It is also an essential source of dietary fiber. The goal of the research was developing bakery products with dietary supplements for a healthy diet. The objects of the research were premium wheat flour and pectin extract obtained from beet pulp, a secondary raw material resource in the production of sugar. When designing new bread products with beet pulp extract, the recipe of traditional wheat bread was taken as a basis. It has been revealed that bread containing beet pulp extract in its recipe in a dosage of 10% by weight of flour has indicators that contribute to the formation of high-quality finished products. This product can be used by all age groups of the population for preventive purposes.The obtained results can be used in any food production involved in the design and production of enriched bakery products using innovative technologies.